Prognostic factors of overall survival for patients with FIGO stage IIIc or IVa ovarian cancer treated with neo-adjuvant chemotherapy followed by interval debulking surgery: A multicenter cohort analysis from the FRANCOGYN study group. Issue 9 (September 2020) - Vincent, L.; Jankowski, C.; Ouldamer, L.; Ballester, M.; Bendifallah, S.; Bolze, P.A.; Akladios, C.; Costaz, H.; Lavoué, V.; Canlorbe, G.; Collinet, P.; Touboul, C.; et al.
Abstract: Introduction: The aim of this study was to identify prognostic factors of overall survival in patients with FIGO stage IIIc or IVa ovarian cancer (OC) treated by neo-adjuvant chemotherapy (NAC) followed by interval debulking surgery. Materials and methods: Data from 483 patients with ovarian cancer were retrospectively collected, from January 1, 2000 to December 31, 2016, from the FRANCOGYN database, regrouping data from 11 centers specialized in ovarian cancer treatment. Median overall survival was determined using the Kaplan-Meier method. Univariate and multivariate analysis were performed to define prognostic factors of overall survival. Results: The median overall survival was 52 after a median follow up of 30 months. After univariate analysis, factors significantly associated with decreased overall survival were; no pelvic and/or para-aortic lymphadenectomy ( p = 0.002), residual disease (CC1/CC2/CC3) after surgery ( p < 0.001), positive cytology after NAC ( p < 0.001), omental disease after NAC ( p = 0.002), no pathologic complete response (pCR) ( p = 0.002). In multivariate analysis, factors significantly associated with decreased overall survival were; residual disease after surgery (HR = 1.93; CI95% (1.16–3.21), p = 0.01) and positive cytology after NAC (HR = 1.59; CI95% (1.01–2.55), p = 0.05). Patients with no residual disease after surgery had a median overall survival of 64 months versus 35 months for patients with residual disease. Patients with negative cytology after NAC had a median overall survival of 71 months versus 43 months for patients with positive cytology after NAC. Conclusion: In this first and largest French based retrospective study, complete cytoreductive surgery in ovarian cancer remains the main prognostic factor of overall survival.